DECONSTRUCTING COLONIAL MEANING IN E.M. FORSTER’S A PASSAGE TO INDIA: A DERRIDEAN READING OF INSTABILITY AND CONTRADICTION (Contemporary Journal of Social Science Review, 2026)
This article applies Jacques Derrida’s theory of Deconstruction to selected passages from E.M. Forster’s A Passage to India. It argues that the novel resists fixed meaning through linguistic instability, contradictory perceptions, and collapsing binary oppositions such as truth/illusion, presence/absence, and colonizer/colonized. Through close textual analysis, the study demonstrates that meaning is continuously deferred and never fully stabilized. The analysis reveals that colonial discourse, identity formation, and narrative authority are inherently unstable. The study concludes that Forster’s text exemplifies Derrida’s concept of différance, where meaning is produced through difference and deferral rather than fixed reference.